Analysis of surgical fixation of displaced proximal humerus fractures using PHILOS plate - Chodavarapu, Lalith Mohan; Kashayi Chowdojirao, Sreekanth; Gonu, Avinash; Patnala, Chandrasekhar; Chilakamarri, Vijay Krishna (International Journal of Research in Orthopaedics, 2016)
Background: The treatment of displaced proximal humeral injuries still throws challenges in identifying variables to prognosticate the outcome and optimizing a good clinical result. This study attempts to analyze the functional outcome of surgery of such fractures with proximal humeral interlocking system (PHILOS) plate and evaluate variables which help in predicting the prognosis. Methods: This is a retrospective and prospective study of 30 patients with displaced proximal humerus fractures - 2 part, 3 part, 4 part and fracture dislocations according to Neer classification, surgically treated using PHILOS plate during 2011 and 2014. Evaluation of patients was done on follow-up by an independent observer for union by radiographs and functional assessment by Constant-Murley score and DASH (disabilities of the arm, shoulder and hand) score. Results: The mean age of the patients was 40.4 years (range 18-65). 83.3% of the patients were male. The mean follow-up was 18.9 months (4-36 months). The mean Constant-Murley score and the DASH score were 76 and 16 respectively at the last follow-up. Our analysis showed that the patient’s age, delay in surgery, and Neer’s classification influenced the prognosis of the fracture. Medial metaphyseal extension in the fracture or an intact medial neck showed a better outcome. Complications were seen in 5 patients. Avascular necrosis was seen in 3 patients. Conclusions: Osteosynthesis of displaced proximal humeral fractures with PHILOS plate provides a good outcome, with low complication rate. Patient’s age and the type of fracture based on Neer’s classification prognosticate the outcome.